Effectivity of Pedada Fruit (Sonneratia caseolaris) Extract to The Level of Sgot and Sgpt in Rat Treated by Paracetamol Induction - Ratih Devi Lestari; R Susanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2015)
The study was aimed to determine the effectiveness of pedada fruit extract as a hepatoprotector in the experimental rat that fed by toxic dose of paracetamol. The total of 30 white rats (Wistar strain, two months age, and 150-200 g weight) were randomly divided into 5 groups. Group I (normal control) only given distilled water for 7 days). Group II (negative control) that given distilled water for 7 days and then treated by 270 mg/head single dose of paracetamol. Group III, IV, and V (treatment group) were given a pedada fruit extract at a dose of 28 mg/head/day, 56 mg/head/day, and 84 mg/head/day for 7 days and then treated by 270 mg/head single dose of paracetamol. On the 9th day of treatment, the blood samples were taken and were further measured for its SGOT and SGPT level using photometry enzymatic method. The result of LSD test on SGOT and SGPT data showed that III, IV, and V groups were not significantly different to the group I (p0.05). However, it significantly different with the group II (p 0.05). Data of SGOT showed that group IV were significantly different (p 0.05) with the group V. Whereas, the data of SGPT among groups III, IV, and V were not significantly different (p0.05). The result of linier regression test indicated that dose 28 mg/head was the most effective dose. It was concluded that pedada fruit extract was able to provide a hepatoprotective effects in rats that fed by toxic dose of paracetamol and most effective dose as a hepatoprotector was 28mg/head/day.Penelitian ini bertujuan untuk mengetahui efektivitas ekstrak buah pedada sebagai hepatorotektor tikus putih yang diberi parasetamol dosis toksik.Sebanyak 30 ekor tikus putih (strain Wistar jantan berumur dua bulan dengan berat badan 150-200 g) dibagi secara acak dalam lima kelompok.Kelompok I (kontrol normal) diberi aquadest selama tujuh hari.Kelompok II (kontrol negatif),diberi aquadest selama tujuh hari dilanjutkan pemberian parasetamol 270 mg/ekor dosis tunggal.Kelompok III, IV, dan V (kelompok perlakuan) diberi ekstrak buah pedada pada dosis 28 mg/ekor/hari, 56 mg/ekor/hari, dan 84 mg/ekor/hari selama tujuh hari dilanjutkan pemberian parasetamol 270 mg/ekor dosis tunggal. Hari ke-9 darah diambil dan diukur kadar SGOT dan SGPT dengan metode fotometri enzimatik. Hasil uji LSD data SGOT dan SGPT menunjukkan bahwa kelompok III, IV, dan V tidak berbeda nyata terhadap kelompok I (p0,05), namun berbeda nyata terhadap kelompok II (p0,05). Data SGOT kelompok IV berbeda nyata (p0,05) dengan kelompok V. Data SGPT tidak ada perbedaan nyata (p0,05) antara kelompok III, IV, dan V. Hasil uji regresi linier, dosis 28 mg/ekor adalah dosis paling efektif.Disimpulkan bahwa ekstrak buah pedada mampu memberikan efek hepatoprotektor pada tikus yang diberi parasetamol dosis toksik dan dosis yang paling efektif sebagai hepatoprotektor adalah dosis 28 mg/ekor/hari.